A review of biodegradable thermoplastic starches, their blends and composites: recent developments and opportunities for single-use plastic packaging alternatives. Issue 22 (3rd November 2022) - Surendren, Aarsha; Mohanty, Amar K.; Liu, Qiang; Misra, Manjusri
Abstract : This review article effectively analyses the effect of multiple plasticizers, compatibilizers, and essential oils on plasticized starch in the preparation of thermoplastic starch-based biodegradable blends and composites. Abstract : Single-use plastic packaging has become an inevitable part of every aspect of human life. In fact, the increase in the consumption of petroleum-based single-use plastics has resulted in the accumulation of municipal solid wastes which are a leading source of plastic pollution worldwide. Biobased materials are a virtuous replacement for single-use petroleum-based packaging products, when recycling is difficult or not practical, to fulfil environmental and economic demands. Starch is an abundant biobased polymeric material that is sustainable and biodegradable. However, the inefficiency of starch in processability due to the existence of hydrogen bonding interactions and intermolecular forces impedes its applications. An effective solution is plasticization of starch in the presence of heat and shear, and is termed plasticized starch (PS). Although different sources may refer to plasticized starch (PS) as thermoplastic starch (TPS), the plasticization process does not make the starch a thermoplastic material until it is blended with toughened polymer, making the nomenclature counterintuitive. TPS is procured through the process of plasticization of starch with water and plasticizers followed by blending with tougher polymers/biopolymers. This could enhance the flexibility and processability of the blend materials, which are an effective replacement for petroleum-based single-use plastic packaging. In this review the main focus is on analysing the effect of multiple plasticizers and compatibility enhancers such as compatibilizers, coupling agents and essential oils in TPS blends, and starch-based composites' preparation and their effective use in single-use packaging applications. Global production and market analysis of thermoplastic starches and their challenges in real-life packaging applications are also discussed.